Regulatable transgenic mouse models of Alzheimer disease: onset, reversibility and spreading of Tau pathology. (22nd April 2013) - Hochgräfe, Katja; Sydow, Astrid; Mandelkow, Eva‐Maria
Abstract : Accumulation of amyloidogenic proteins such as Tau is a hallmark of neurodegenerative diseases including Alzheimer disease and fronto‐temporal dementias. To link Tau pathology to cognitive impairments and defects in synaptic plasticity, we created four inducible Tau transgenic mouse models with expression of pro‐ and anti‐aggregant variants of either full‐length human Tau (hTau40/ΔK280 and hTau40/ΔK280/PP) or the truncated Tau repeat domain (TauRD /ΔK280 and TauRD /ΔK280/PP). Here we review the histopathological features caused by pro‐aggregant Tau, and correlate them with behavioral deficits and impairments in synaptic transmission. Both pro‐aggregant Tau variants cause Alzheimer‐like features, including synapse loss, mis‐localization of Tau into the somatodendritic compartment, conformational changes and hyperphosphorylation. However, there is a clear difference in the extent of Tau aggregation and neurotoxicity. While pro‐aggregant full‐length hTau40/ΔK280 leads to a 'pre‐tangle' pathology, the repeat domain TauRD /ΔK280 causes massive formation of neurofibrillary tangles and neuronal loss in the hippocampus. However, both Tau variants cause co‐aggregation of human and mouse Tau and similar functional impairments. Thus, earlier Tau pathological stages and not necessarily neurofibrillary tangles are critical for the development of cognitive malfunctions. Most importantly, memory and synapses recover after switching off expression of pro‐aggregant Tau. The rescue of functional impairments correlates with the rescue of most Tau pathological changes and most strikingly the recovery of synapses. This implies that tauopathies as such are reversible, provided that amyloidogenic Tau is removed. Therefore, our Tau transgenic mice may serve as model systems for in vivo validation of therapeutic strategies and drug candidates with regard to cognition and synaptic function. Abstract : The review deals with the onset, reversibility and spreading of Tau pathology observed in Tau transgenic mouse models. We summarize histopathological features caused by inducible expression of pro‐aggregant Tau and correlate them to behavioral deficits and impairments in synaptic transmission, which recover after removal of amyloidogenic Tau. Furthermore we discuss mechanisms of Tau spreading and transmission throughout mouse brain regions.